2021
DOI: 10.3390/met11071137
|View full text |Cite
|
Sign up to set email alerts
|

Non-Isothermal Reduction Kinetics of Iron Ore Fines with Carbon-Bearing Materials

Abstract: This study investigates the non-isothermal reduction of iron ore fines with two different carbon-bearing materials using the thermogravimetric technique. The iron ore fines/carbon composites were heated from room temperature up to 1100 °C with different heating rates (5, 10, 15, and 20 °C/min) under an argon atmosphere. The effect of heating rates and carbon sources on the reduction rate was intensively investigated. Reflected light and scanning electron microscopes were used to examine the morphological struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The peculiarity of the medium basicity sinter is that despite its high mechanical strength, it tends to collapse in the upper part of the blast furnace shaft. It has been found that the decisive factor in this destruction is the reduction process: the maximum destruction is observed at a reduction rate of 25-40%, that is, at the stage of reduction Fe 2 O 3 →Fe 3 O 4 (which corresponds to temperatures of 500-700 • C, at higher temperatures, the softening slows down, and at temperatures above 900 • C, the strength even increases) [38]. Material destruction during reduction by carbon monoxide occurs more strongly than during reduction by hydrogen [39].…”
Section: Relationship Between Structure and Metallurgical Characteris...mentioning
confidence: 99%
“…The peculiarity of the medium basicity sinter is that despite its high mechanical strength, it tends to collapse in the upper part of the blast furnace shaft. It has been found that the decisive factor in this destruction is the reduction process: the maximum destruction is observed at a reduction rate of 25-40%, that is, at the stage of reduction Fe 2 O 3 →Fe 3 O 4 (which corresponds to temperatures of 500-700 • C, at higher temperatures, the softening slows down, and at temperatures above 900 • C, the strength even increases) [38]. Material destruction during reduction by carbon monoxide occurs more strongly than during reduction by hydrogen [39].…”
Section: Relationship Between Structure and Metallurgical Characteris...mentioning
confidence: 99%
“…There are two different types of composites were prepared which are made of iron ore fines and charcoal, respectively. Magnetite reduction with coal was discovered to be lean, resulting in poorer metallization; yet, the concentrate's increased iron-oxide content and also increases the iron extraction in terms of performance as compared to charcoal [69]. Regardless of thermal conditions, iron ore is reduced under the same heating rate, and coal has a lower reduction rate compared to charcoal.…”
Section: Reduction Of Iron Ore Using Non-coking Coal/charcoalmentioning
confidence: 99%
“…Iron oxide pellet fines utilized in this research were obtained from the transportation and handling of iron oxide pellets in the DR plant (Al-Ezz El-Dekheila steel Company, Alexandria, Egypt). The chemical composition, mean particle size, and main phases of iron oxide pellet fines are illustrated elsewhere [36].…”
Section: Iron Oxide Pellet Finesmentioning
confidence: 99%
“…During the second step, the reduction process is dominated by the chemical reaction, whereas the coupled solid-state diffusion and boundary reaction control the final stage. The reduction of iron ore fines with different carbon sources was investigated non-isothermally using different heating rates by Hammam et al [36]. It was concluded that the heating rates have a significant influence on the conversion degree and the rate of reduction.…”
Section: Introductionmentioning
confidence: 99%